Multi-Platform Detection of Small Ruminant Lentivirus Antibodies and Provirus as Biomarkers of Production Losses - Echeverría, Irache; De Miguel, Ricardo; De Pablo-Maiso, Lorena; Glaria, Idoia; Benito, Alfredo A.; De Blas, Ignacio; De Andrés, Damián; Luján, Lluís; Reina, Ramsés (Frontiers in Veterinary Science, 2020)
Small ruminant lentiviruses (SRLV) are endemic in most areas of Europe causing a chronic infection and a multisystemic disease affecting udder, carpal joints, lungs and central nervous system. Due to the lack of treatments and protective vaccination strategies, infection control is focused on the identification of infected animals through serological or molecular techniques. However, antigenic and genetic heterogeneity of SRLVs represent a clear drawback for diagnosis. Infected animals may present lower animal production parameters such as birth weight or milk production and quality, depending on productive systems considered and likely, to the diagnostic method applied. In this study, four sheep flocks dedicated to dairy or meat production were evaluated using three different ELISA and two PCR strategies to classify animal population attending to SRLV infection status. Productive parameters were recorded along one whole lactation or reproductive period and compared between positive and negative animals. SRLV was present in 19% of the total population being unequally distributed in the different flocks. Less than half of the infected animals were detected by a single diagnostic method, highlighting the importance of combining different diagnostic techniques. Statistical analysis employing animal classification using all the diagnostic methods associated lambing size, lamb weight at birth and daily weight gain with SRLV infection status in meat flocks. Milk production, somatic cell count, fat and protein content in the milk were associated with SRLV infection in dairy flocks, to a greater extent in the flock showing higher seroprevalence. A multi-platform SRLV diagnostic strategy was useful for ensuring correct animal classification, thus validating downstream studies investigating production traits.